The Effect of The Implementation of Good Governance and Internal Control on The Performance of Local Government Financial Management in Palopo City - Sabnur, Aulia Ihfa; Usman, Halim; Dasila, Rifqa Ayu (PT. EQUATOR SINAR AKADEMIA, 2025)
Financial management in local governments plays a crucial role in achieving development goals and improving the welfare of local communities. To achieve optimal performance in financial management, local governments are expected to adopt good governance principles and implement an effective internal control system. This study aims to analyze the impact of the implementation of good governance and internal control on the financial management performance of local governments in Palopo City. A quantitative method was used with data collected through questionnaires distributed to 50 employees at the Regional Financial and Asset Management Agency (BPKAD) and the Inspectorate of Palopo City. The results of the study indicate that internal control and the implementation of good governance have a positive effect on financial management performance.